Information Strategies for Communicators - Hansen, Kathleen A.; Paul, Nora; Open Textbook Library (Open Textbook Library, 2015)
Written by two nationally recognized experts in information strategy, Information Strategies for Communicators leads students step-by-step through the information search and evaluation process for news and strategic communication message production. The book includes a conceptual model of the information strategy process, case studies to illustrate the process in action, and links to current examples throughout. The definitive text for the information search and evaluation process as practiced by news and strategic communication message producers. Currently used at the University of Minnesota School of Journalism and Mass Communication; JOUR 3004W/V, Information for Mass Communication.
Lesson 1. Personal / Professional Skills of Successful Communicators -- Lesson 2. Information Strategy Process and the Needs of Communicators -- Lesson 3. Question Analysis: From Assignment to Message -- Lesson 4. Question Analysis: Who's the Audience? -- Lesson 5. Question Analysis: What's the Topic? -- Lesson 6. Question Analysis: Who Contributes Information? -- Lesson 7. Question Analysis: What are the Ethical and Legal Considerations? -- Lesson 8. Research Skill: Searching -- Lesson 9. Research Skill: Interviewing -- Lesson 10. Research Skill: Evaluating Information -- Lesson 11. Research Skill: Managing and Synthesizing Information -- Lesson 12. Information Resources: Publications -- Lesson 13. Information Resources: Public Records -- Lesson 14. Information Resources: Data and Statistics -- Lesson 15. Information Resources: Polls and Surveys -- Lesson 16. Message Tasks: Applying What You've Learned
In English.
Description based on print resource
Keywords: Communication -- Textbooks